2009
DOI: 10.1007/s10447-008-9067-8
|View full text |Cite
|
Sign up to set email alerts
|

Counseling and Family Therapy in India: Evolving Professions in a Rapidly Developing Nation

Abstract: Outpatient counseling is a relatively new concept and form of clinical practice in India. This article provides an overview of the need for and current status of counseling and family therapy in India. Examples of training programs are presented, and future prospects for the counseling and family therapy professions are highlighted. The authors discuss therapeutic issues that clinicians may need to consider when working with Indian clients, as well as some of the potential barriers to counseling individuals, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Family and couple's conflict arising out of factors such as conflicts in families over dowry, or related to inter-caste marriage; sexual problems arising out of physical separation of couples due to job timing or placement; disagreement about child rearing practices (both within couples and intergenerational); conflicts related to husband's role in sharing in domestic chores for working couples; problems with unsupervised children, and loss or displacement of role or function of the elderly are only a few of the problems unique to modern Indian families. [90] In family therapy focusing on adolescent and children, substance abuse, juvenile delinquency, school dropout or low school attendance are common amongst the lower socioeconomic classes. Parent-child conflict from increased autonomy and individuation of the child are common in nuclear families.…”
Section: Understanding Psychotherapy From the Family Perspectivementioning
confidence: 99%
“…Family and couple's conflict arising out of factors such as conflicts in families over dowry, or related to inter-caste marriage; sexual problems arising out of physical separation of couples due to job timing or placement; disagreement about child rearing practices (both within couples and intergenerational); conflicts related to husband's role in sharing in domestic chores for working couples; problems with unsupervised children, and loss or displacement of role or function of the elderly are only a few of the problems unique to modern Indian families. [90] In family therapy focusing on adolescent and children, substance abuse, juvenile delinquency, school dropout or low school attendance are common amongst the lower socioeconomic classes. Parent-child conflict from increased autonomy and individuation of the child are common in nuclear families.…”
Section: Understanding Psychotherapy From the Family Perspectivementioning
confidence: 99%
“…The data obtained presents a detailed assessment of the various cultural signifiers and worldviews that counsellors had to accommodate. While existing research, Carson et al (2009), had identified family as a major factor it had not identified it as playing a central role in religiousandcultural attitudes. Families saw therapy as foreign or threatening.…”
Section: Discussionmentioning
confidence: 99%
“…He suggests developing a culturally relevant and dynamic model from both traditions, equipped to deal with Indian conditions. Carson, Jain and Ramirez (2009) note that the family, the central influence within Indian society, is inadequately addressed in terms of the educational and training available to counsellors while the need for family counselling exists. They note that counsellingis poorly funded, supported by few institutions andthe idea that mental health issues are due to consumerism hinder the development of the mental health profession in India.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Within Kenya, Nigeria, India, Fiji and Vietnam for example, brief workshops, certificates of training and undergraduate degrees serve as the primary pedagogical models for educating and equipping persons to do the work of counseling (Aluede et al 2005;Auxier et al 2005;Carson et al 2009;Le 2009;Okech and Kimemia 2011;Raney and Cinarbas 2005). In most countries outside the U.S., there is an absence of uniform standards and accrediting bodies to provide oversight for education and training.…”
Section: Extant Literaturementioning
confidence: 98%